2019
DOI: 10.4037/ajcc2019170
|View full text |Cite
|
Sign up to set email alerts
|

CORTRAK Superuser Competency Assessment and Training Recommendations

Abstract: Background Blind insertion of feeding tubes remains unsafe. Electromagnetic placement devices such as the CORTRAK Enteral Access System allow operators to interpret placement of feeding tubes in real time. However, pneumothoraces have been reported and inadequate user expertise is a concern. Objective To explore factors influencing competency of CORTRAK-assisted feeding tube insertion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…However, it is known that patients scratch their nose due to the itchy sensation of the tape resulting in the removal of the tube. Important points as identified by Bourgault et al (2019) were to correctly identify the patient and any contra-indications for tube insertion such as basal skull fracture or coagulation derangements. The head of bed at 30-45 degrees was also important for successful insertion as with all nasogastric tubes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that patients scratch their nose due to the itchy sensation of the tape resulting in the removal of the tube. Important points as identified by Bourgault et al (2019) were to correctly identify the patient and any contra-indications for tube insertion such as basal skull fracture or coagulation derangements. The head of bed at 30-45 degrees was also important for successful insertion as with all nasogastric tubes.…”
Section: Discussionmentioning
confidence: 99%
“…In Bourgault and colleagues' observational pilot study, they reported previously trained RNs (n = 20) self-reported needing to complete 8 SBFT placements with an EMPD before they felt confident performing this procedure. 30 Interpretation of the insertion tracing was the most commonly observed operator error reported, and the RNs in this cohort self-identified needing to complete 10 placements before "confidence" was established. These authors also suggested that at least 3 observations should be performed to assess initial competency; however, that number may need to be individualized.…”
Section: Training and Competencymentioning
confidence: 96%
“…These authors also suggested that at least 3 observations should be performed to assess initial competency; however, that number may need to be individualized. 30 Initial, annual, and/or ongoing competency evaluation is required to ensure the RDN/RN is compliant with policies and procedures, understands techniques, and has developed critical thinking skills for evaluating patient safety or other clinical concerns. Maintaining competency in the placement of SBFTs is especially important for RDNs/RNs who may not have the opportunity to place them on a daily or even weekly basis.…”
Section: Training and Competencymentioning
confidence: 99%
“…By placing NE tubes more frequently, clinicians likely become more proficient at this skill and are able to practice at the expert level. Often, these clinicians are designated as a “super user.” A “super user” can be defined as a core team member who is trained, independent, and a validated operator of a feeding tube placement device 90 . This model may work better for smaller healthcare facilities with lower numbers of feeding tube placement orders or for training medical staff.…”
Section: Practitioners Placing Bedside Feeding Tubesmentioning
confidence: 99%
“…In an observational pilot study, Bourgault et al identified previously trained RNs (n = 20) who, through self‐report, estimated that they needed to complete a mean of eight tube placements with an EMPD before they felt confident performing this procedure 90 . Interpretation of the insertion tracing was the most commonly observed operator error reported, and the RNs in this cohort self‐reported needing to complete a mean of 10 placements before “confidence” was established.…”
Section: Practitioners Placing Bedside Feeding Tubesmentioning
confidence: 99%